2000
DOI: 10.1542/peds.105.3.492
|View full text |Cite
|
Sign up to set email alerts
|

Predicting First-Year Relapses in Children With Nephrotic Syndrome

Abstract: We conclude that of all the presenting features, the rapidity of initial response to steroid therapy combined with the presence of hematuria, could predict future relapses and should be well documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
35
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 13 publications
12
35
2
5
Order By: Relevance
“…It was shown in a similar study that prognosis would be better in children going into early remission with steroid medication. [13] Infectious episodes in nephrotic patients are responsible for high morbidity and can also cause an inadequate response to corticosteroid therapy and recurrences among patients in remission. [14] In our patients, similar to the frequency of having infection, frequency of relapse has increased significantly (r=0.44; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in a similar study that prognosis would be better in children going into early remission with steroid medication. [13] Infectious episodes in nephrotic patients are responsible for high morbidity and can also cause an inadequate response to corticosteroid therapy and recurrences among patients in remission. [14] In our patients, similar to the frequency of having infection, frequency of relapse has increased significantly (r=0.44; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…T he annual incidence of idiopathic nephrotic syndrome (INS) in children is 2-7 /100,000 populations below 1-16 years of age 1 . The patients are usually treated with oral prednisolone as per APN protocol (prednisolone 60 mg/m 2 /day for 6 weeks, followed by 40 mg/m 2 /every alternate days for 6 weeks) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The relapses are often precipitated by infections 6,9,14 which become troublesome for the patients as well as parents. Certain factors such as age, gender, time to response, duration of treatment of initial episode and frequency of relapses in the initial six months have been found to predict the relapses in these patients 1,10,16 . However, there has been inconsistency in the literature and also paucity of reports from our country to determine precisely that which factors are really responsible for, and reliably predict the relapses.…”
Section: Introductionmentioning
confidence: 99%
“…The records of 125 children with steroid responsive INS were retrospectively studied; out of which 38 children (23.4 %) were steroid dependent. It was found that time duration of remission (<10 d) from start of therapy (p 0.00, OR= 1.1, 95 % CI=1.0-1.1) and steroid regime other than 6 wk daily (2 mg/kg)+6 wk alternate day (1.5 mg/kg) (p 0.01, OR= 5.6, 95 % CI=1.3-24.3) were found as significant predictors.The relapsing nature of the disease presents a major challenge, and 60 % of the patients have a high relapse rate [3], with a subsequent risk of steroid toxicity and complications and with half of those relapsing eventually becoming steroid dependent [4].By early identification of those children who are likely to develop steroid dependency and its attendant morbidity, the attending clinician will be able to plan the long term management of these children and minimizing the steroid side effects. …”
mentioning
confidence: 99%
“…The relapsing nature of the disease presents a major challenge, and 60 % of the patients have a high relapse rate [3], with a subsequent risk of steroid toxicity and complications and with half of those relapsing eventually becoming steroid dependent [4].…”
mentioning
confidence: 99%